2013
DOI: 10.1186/1471-2407-13-564
|View full text |Cite
|
Sign up to set email alerts
|

Long-lasting response to electrochemotherapy in melanoma patients with cutaneous metastasis

Abstract: BackgroundTreatment of early and multiple cutaneous unresectable recurrences is a major therapeutic problem with around 80% of patients relapsing within 5 years. For lesions refractory to elective treatments, electrochemotherapy (ECT) involving electroporation combined with antineoplastic drug treatment appears to be a new potential option. This study was undertaken to analyze the short- and long-term responses of lesions treated with ECT with intravenous injection of bleomycin in melanoma patients with in-tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 21 publications
4
34
0
Order By: Relevance
“…Caracò et al . reported that 45% of complete responders experienced a long‐lasting response after one ECT session and were disease free after a mean follow‐up of 27·5 months . In our study, as well as in former published studies, the clinical activity of ECT was accompanied with a favourable toxicity profile with no severe side‐effects.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Caracò et al . reported that 45% of complete responders experienced a long‐lasting response after one ECT session and were disease free after a mean follow‐up of 27·5 months . In our study, as well as in former published studies, the clinical activity of ECT was accompanied with a favourable toxicity profile with no severe side‐effects.…”
Section: Discussionsupporting
confidence: 82%
“…Several studies have investigated the effectiveness of ECT . A study on the efficacy and safety of ECT published in 2006 by Mir et al .…”
mentioning
confidence: 99%
“…Therefore, the patient underwent conservative surgery, which allowed sparing the oral mucosa and the floor of the orbit, while the reconstruction was easily obtained by means of a rotation flap. At 1-year followup, the patient was disease-free, with good functional and esthetic results, as confirmed by CT and FDG PET/CT (29). This is a single patient case report, whose results should be confirmed by other studies.…”
Section: Melanomasupporting
confidence: 63%
“…In 2008, Curatolo et al reported ECT of a local recurrence of penile Kaposi sarcoma (KS), with a CR and no signs of local relapse 14 months after completion of the treatment (30). These data suggest that ECT could be a valid alternative to surgery, especially in difficult anatomical sites.…”
Section: Kaposi Sarcomamentioning
confidence: 99%
“…Electrochemotherapy is a standard treatment in many cancer centers around Europe that potentiates the delivery of cytotoxic drugs by local electric pulses delivery (http://guidance. nice.org.uk/IPG446) (5). This strategy is also promising for the systemic secretion of therapeutic proteins.…”
Section: Introductionmentioning
confidence: 99%